The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.0022-3646.2003.02-141.x
|View full text |Cite
|
Sign up to set email alerts
|

HERITABILITY OF MANTLE AREOLAR CHARACTERS IN AULACOSEIRA SUBARCTICA (BACILLARIOPHYTA)1

Abstract: Are size and arrangement of valve mantle areolae in Aulacoseira Thwaites adapted to light intensity? To test one criterion demonstrating an adaptation, heritability experiments were run on isolates of Aulacoseira subarctica (Müller) Haworth. Several clones of A. subarctica were isolated from Yellowstone Lake (Wyoming, USA), Lewis Lake (Wyoming), and East Rosebud Lake (Montana, USA). Two to four clones from each lake were grown in batch cultures under three irradiance levels: 2, 11.4, and 115 lmol photons . m À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Experimental studies provide some support for this hypothesis. Provided sufficient genetic variation in phenotypic traits for selection to act on, a rapid evolutionary response can be predicted (Wood et al, 1987(Wood et al, , 2005Edgar and Theriot, 2003). Moreover, several authors have suggested that the seemingly cosmopolitan distribution and maintenance of relatively high abundances of many species of phytoplankton result from changes in genotype composition within species (cf.…”
Section: A D a P T I V E E V O L U T I O N I N R E S P O N S E T O E mentioning
confidence: 99%
“…Experimental studies provide some support for this hypothesis. Provided sufficient genetic variation in phenotypic traits for selection to act on, a rapid evolutionary response can be predicted (Wood et al, 1987(Wood et al, , 2005Edgar and Theriot, 2003). Moreover, several authors have suggested that the seemingly cosmopolitan distribution and maintenance of relatively high abundances of many species of phytoplankton result from changes in genotype composition within species (cf.…”
Section: A D a P T I V E E V O L U T I O N I N R E S P O N S E T O E mentioning
confidence: 99%
“…Since virtually every diatom species is inextricably linked to a morphological, character-based definition, candidates for mating experiments are chosen on the basis of their characters, which suggests some level of confidence in the character-based classification. Note also that classic heritability studies still provide an excellent way to explore the potential evolutionary importance of morphological characters in diatoms (Edgar and Theriot 2003;Wood et al 1987). A positive trend in BSC-based diatom research is the increasing number of studies that cite direct evidence from mating experiments (Amato et al 2007;Behnke et al 2004;Mann et al 2004;Vanormelingen et al 2007Vanormelingen et al , 2008, rather than indirect character-based evidence, to support species boundaries under the BSC.…”
Section: The Biological Species Conceptmentioning
confidence: 99%
“…The genus may extend back to the Late Cretaceous (Ambwani et al, 2003). Edgar and Theriot (2004) conducted a phylogenetic analysis of Aulacoseira using morphological and molecular data and studied the heritability of valve mantle features (Edgar and Theriot, 2003).…”
Section: Generamentioning
confidence: 99%